2009
DOI: 10.1016/j.ergon.2008.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Hand-skin temperature and tracking performance

Abstract: Even though manual tracking performance has been extensively investigated, there is little or no research related to the lower limit of temperature for unimpaired tracking performance.This study sought to obtain temperature limits while investigating the effect of hand-skin temperature on manual tracking. Eighteen subjects participated in a within-subject design

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Note that, as was found in the experiments of Goonetilleke and Hoffmann (2008), the errors are related to the inverse of the squared effective track width. Goonetilleke and Hoffmann have suggested that the errors depend on hand tremor while traversing such a constrained path.…”
Section: Errors In Traversing the Mazesupporting
confidence: 60%
See 1 more Smart Citation
“…Note that, as was found in the experiments of Goonetilleke and Hoffmann (2008), the errors are related to the inverse of the squared effective track width. Goonetilleke and Hoffmann have suggested that the errors depend on hand tremor while traversing such a constrained path.…”
Section: Errors In Traversing the Mazesupporting
confidence: 60%
“…The increase in errors is unlikely to be due to problems of manipulating the pen, as it would be expected that the grip and control of the pen would be better at the larger sizes (Kao, 1979;Udo et al, 2000). As Goonetilleke and Hoffmann (2008) have suggested, the denominator of the error relationship may arise from tremor in the hand and wrist controlling the motion of the pen. Here the level of tremor should have remained approximately constant, so the error increases may have arisen from the variations in the width of the maze track.…”
Section: Discussion Of Experimentsmentioning
confidence: 99%
“…The model has been further verified by Goonetilleke and Hoffmann (2008) in other situations as well.…”
Section: ( ) = (2)mentioning
confidence: 97%
“…That fact is associated with the type and number of layers as well as the surface density of the materials used in the various structural elements of the glove [11]. In addition, the amount of perspiration exuded by the hand skin may increase or decrease depending on the ambient temperature, work strain (light or strenuous manual labor), and individual differences [12,13]. According to the literature, the optimum conditions inside protective gloves are RH ≤ 50% and T ≤ 33°C for light manual work and RH ≤ 80% and T ≤ 33°C for intensive manual work.…”
Section: Introductionmentioning
confidence: 99%